Teaching Reading Comprehension Strategies In Descriptive Text - Fadhlan Saini; Nur Halimah; Astried Herawati Basala (Journal of English Language Teaching, Linguistics, and Literature Studies, 2021)
This research aimed to find out the strategies of English teacher in teaching reading comprehension in descriptive text and to reveal the implementation of the strategies in teaching reading comprehension in descriptive text. In this research, the researcher utilized case study method by using observation, interview and documentation to collect the data. To analyze the data , the researcher utilized three steps of actions. The first action was to observe students and teacher activities during leaning of reading comprehension in descriptive text, the second action was interview the English teacher and students and the last action was done by taking documentation. The respondent of this research was one English teacher and tenth grade students which consisted of 11 students in SMKN 1 Kotabunan Bolaang mongondow Timur. The results of this research indicate that English teacher composed two teaching strategies, namely reading guide and question guide. The fisrt strategy like reading guide strategy made easier for students to understand descriptive text. Meanwhile, the second strategy like question guide strategy was used to determine students' abilities through questions about descriptive texts Keywords: teaching stratgies, reading comprehension, descriptive text